ANALYSIS AND SIMULATION OF VACCINATION QUEUE SYSTEM AT XYZ PUBLIC HEALTH CENTER - Majid, Gean Lahuddin; Swilugar, Ayu; Napilah, Hikmah Goyatun; Deria, Popy Primaviani Desi; Madenda, Gidya; Ferdian, Rendiyatna (CENTRAL ASIA AND THE CAUCASUS, 2022)
This study discusses the vaccination system at XYZ Public Health Center. Vaccination activities at the site through several stages of service, registration, health check, vaccination, observation with the printing of vaccination cards. The vaccination system at XYZ Public Health Center experienced long lines that caused a crowd that should be avoided, especially on registration servers that were done manually. This research aims to determine the best scenario that can be obtained through the analysis of the results of simulated queue models as an alternative decision in optimizing the UPTD vaccination service system of Puskesmas XYZ. The best-case scenario selection analysis is based on consideration of aspects of average service time that aim to reduce the number of queues on service servers. The queue model at existing conditions has 4 officers on registration, 5 officers on inspection, 5 officers on vaccinations, and 4 officers on observation and printing. Based on the results of the analysis can be concluded that the model of the queue system with the number of 5 officers on registration, 2 officers on health check, 2 officers on vaccination, and 1 officer on observation has the best queue system model. The proposed queue system model is able to minimize the crowd that occurson the service server by reducing the service time from existing conditions by 4523.38 seconds to 1401.92 seconds. The proposed improvement with the queue model is also able to increase productivity from 37% to 57% with an increase of 20% from existing conditions, as well as reduce working wages from Rp3,800,000 per day to Rp1,800,000 per day.